Blockchain technology adoption in the supply chain (UTAUT2 with risk) – evidence from Indian supply chains. (30th April 2020) - Sheel, Ashutosh; Nath, Vishnu
The aim of the present study is to study blockchain technology adoption intentions by supply chain practitioners using the unified theory of adoption and use of technology (UTAUT2) with risk model as the conceptual framework. UTAUT2 is generic model which can be used to study adoption of technologies. The present study applies this model to study blockchain technology adoption in the supply chain. Data was collected from 360 supply chain practitioners in India. The results of the current study indicate that behavioural intentions for blockchain technology adoption are significantly influenced by performance expectancy, social influence, hedonic motivation and price value considerations. The study proposes some guidelines for adopting blockchain in the supply chain. The present study tries to fill in the gap in the existing literature by listing out the factors that influence blockchain technology adoption in the supply chain.